Online victimization - an explorative study of sexual violence and cyber grooming in the context of social media use by young adults in Germany - Sophie Weingraber; Christina Plath; Laura Naegele; Margit Stein (Social Work & Society, 2021)
Current studies on cyber grooming mainly relate to children approached by older people on social media with the aim of sexual abuse. Only a few studies exist in Germany, but they don't focus on the cyber grooming of peers. In the present study, we examine the role of cyber grooming experiences of young adults. Attention is also paid to whether the respondents were affected by cyber grooming in adolescence. The exploratory study includes a sample of 300 young adults aged between 18 to 25 years. Overall, 208 are female and 90 are male (nother gender= 2). X2-tests prove that gender is, in particular, a predictor for experiencing cyber grooming. Furthermore, it is shown that a high educational level is also not a decisive factor in victimization.